2011
DOI: 10.1063/1.3517313
|View full text |Cite
|
Sign up to set email alerts
|

A new ab initio potential energy surface for the NeCO complex with the vibrational coordinate dependence

Abstract: A new high quality three-dimensional potential energy surface for the Ne-CO van der Waals complex is developed using the CCSD(T) method and avqz/avqz+33221 basis set. The ab initio calculation is performed in a total of 1365 configurations with supermolecule method. There is a single global minimum located in a nearly T-shaped geometry. The global minimum energy is −49.4090 cm −1 at R e = 6.40a 0 and θ e = 82.5• for V 00 . Using the three-dimensional potential energy surface, we have calculated bound rovibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…For every temperature the cross sections from Carty et al taken in a He bath gas are 2 -3 times smaller than those reported here with an Ar bath gas. This trend follows the relative magnitudes of the CO-He, CO-Ne and CO-Ar van der Waals wells, which are calculated to be 22.34 cm -1 [46], 49.4 cm -1 [47], 107.1 cm -1 [20] respectively. A deeper van der Waals well increases the strength of the interaction between CO and the noble gas and the likelihood of inelastic collisions.…”
Section: Total Removal Cross-sectionsmentioning
confidence: 99%
“…For every temperature the cross sections from Carty et al taken in a He bath gas are 2 -3 times smaller than those reported here with an Ar bath gas. This trend follows the relative magnitudes of the CO-He, CO-Ne and CO-Ar van der Waals wells, which are calculated to be 22.34 cm -1 [46], 49.4 cm -1 [47], 107.1 cm -1 [20] respectively. A deeper van der Waals well increases the strength of the interaction between CO and the noble gas and the likelihood of inelastic collisions.…”
Section: Total Removal Cross-sectionsmentioning
confidence: 99%